1978
DOI: 10.1063/1.325498
|View full text |Cite
|
Sign up to set email alerts
|

Volumetric study of the α→α′ phase transformation of cerium and its implications regarding the crystal structure of α′-cerium.

Abstract: The volume change of cerium metal at the α→α′ phase transformation at 51 kbar is found to be (1.5±1) % from macroscopic measurements made in the sliding-anvil apparatus SAD 2. This value supports the proposal by Zachiarasen and Ellinger that the high-pressure forms of cerium above 51 kbar are a stable orthorhombic form with the α-uranium type of structure and a metastable monoclinic body-centered form with a deformed face-centered structure and invalidate all the other crystal structures reported so far for α′… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1979
1979
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Upon further compression at RT, Ce undergoes a phase transition, at ∼4 GPa. Early x-ray diffraction experiments reported that the transition is to a C-centered orthorhombic structure (oC 4 in Pearson notation and denoted α in the literature), isostructural with that found in α-uranium at ambient conditions [12,13]. Subsequent x-ray studies [14,15], however, concluded that Ce transforms to a C-centered monoclinic structure (mC 4 in Pearson notation and denoted α in the literature), while others observed both the oC 4 and mC 4 structures [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Upon further compression at RT, Ce undergoes a phase transition, at ∼4 GPa. Early x-ray diffraction experiments reported that the transition is to a C-centered orthorhombic structure (oC 4 in Pearson notation and denoted α in the literature), isostructural with that found in α-uranium at ambient conditions [12,13]. Subsequent x-ray studies [14,15], however, concluded that Ce transforms to a C-centered monoclinic structure (mC 4 in Pearson notation and denoted α in the literature), while others observed both the oC 4 and mC 4 structures [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Under these conditions, calculations show that pressures of 20 GPa can be obtained. Experiments confirmed that pressures of 20 GPa could be reached in this device [21], but this pressure is expected to be the approximate limit for this kind of apparatus with tungsten carbide anvils.…”
Section: The Large Anvilsmentioning
confidence: 74%